2021
DOI: 10.1038/s41467-020-20573-7
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of aberrant splicing events in RNA-seq data using FRASER

Abstract: Aberrant splicing is a major cause of rare diseases.  However, its prediction from genome sequence alone remains in most cases inconclusive. Recently, RNA sequencing has proven to be an effective complementary avenue to detect aberrant splicing. Here, we develop FRASER, an algorithm to detect aberrant splicing from RNA sequencing data. Unlike existing methods, FRASER captures not only alternative splicing but also intron retention events. This typically doubles the number of detected aberrant events and identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 64 publications
0
124
0
Order By: Relevance
“…A |Δ ψ| > 0.3 is recommended as an additional filter for the identification of pathological-relevant variation, where it corresponds to the difference between the observed ψ and the expected ψ. Application of FRASER in the rare disease cohort from Kremer et al (2017) identified all three previously detected pathogenic splicing aberrations, plus an intron-retention event missed by LeafCutter, and a synonymous variant causing a splice defect missed by Kremer et al (Mertes et al, 2021). FRASER was also applied to the GEUVADIS multicenter and multi-ancestry cohort and was able to remove sample covariation for all metrics (Yépez et al, 2021b).…”
Section: Splicing Outliersmentioning
confidence: 99%
See 4 more Smart Citations
“…A |Δ ψ| > 0.3 is recommended as an additional filter for the identification of pathological-relevant variation, where it corresponds to the difference between the observed ψ and the expected ψ. Application of FRASER in the rare disease cohort from Kremer et al (2017) identified all three previously detected pathogenic splicing aberrations, plus an intron-retention event missed by LeafCutter, and a synonymous variant causing a splice defect missed by Kremer et al (Mertes et al, 2021). FRASER was also applied to the GEUVADIS multicenter and multi-ancestry cohort and was able to remove sample covariation for all metrics (Yépez et al, 2021b).…”
Section: Splicing Outliersmentioning
confidence: 99%
“…Bearing in mind the limitations of the approaches described, three specialized methods to systematically detect aberrant splicing were developed: FRASER, LeafCutterMD, and SPOT. FRASER (Find Rare Splicing Events in RNAseq) is an approach combining machine learning and statistical models to detect aberrant splicing from RNAseq data (Mertes et al, 2021). Using the same rationale as OUTRIDER for detecting aberrant expression, FRASER uses a denoising autoencoder automatically controlling for latent confounders.…”
Section: Splicing Outliersmentioning
confidence: 99%
See 3 more Smart Citations